2015
DOI: 10.18632/oncotarget.4673
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying signaling pathway activation to monitor the quality of induced pluripotent stem cells

Abstract: Many attempts have been made to evaluate the safety and potency of human induced pluripotent stem cells (iPSCs) for clinical applications using transcriptome data, but results so far have been ambiguous or even contradictory. Here, we characterized stem cells at the pathway level, rather than at the gene level as has been the focus of previous work. We meta-analyzed publically-available gene expression data sets and evaluated signaling and metabolic pathway activation profiles for 20 human embryonic stem cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…It has been used to analyze parallels in pathway activation between pathological and chronological aging in Hutchinson-Gilford Progeria Syndrome fibroblasts, a disease-based model of aging [ 36 ]. It has also been used in evaluating the therapeutic viability of pluripotent stem cells [ 37 ] and in cross-species analysis [ 38 ], an important aspect of aging research [ 30 ]. Additionally it has helped determine common pathway signatures in lung and liver fibrosis [ 39 ] and evaluate pro-fibrotic pathway activation in trabecular meshwork and lamina cribrosa in glaucoma [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been used to analyze parallels in pathway activation between pathological and chronological aging in Hutchinson-Gilford Progeria Syndrome fibroblasts, a disease-based model of aging [ 36 ]. It has also been used in evaluating the therapeutic viability of pluripotent stem cells [ 37 ] and in cross-species analysis [ 38 ], an important aspect of aging research [ 30 ]. Additionally it has helped determine common pathway signatures in lung and liver fibrosis [ 39 ] and evaluate pro-fibrotic pathway activation in trabecular meshwork and lamina cribrosa in glaucoma [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“… 19 It was shown to be efficient in finding new cancer biomarkers, more stable than individual gene expression patterns. 11 To date, OncoFinder was applied for many objects including induced pluripotent stem cells, 20 leukemia and solid cancers, 21,22,23 Hutchinson Gilford Disease, 24 and Age-Related Macular Degeneration Disease. 25 …”
Section: Introductionmentioning
confidence: 99%
“…What could be the factors serving as roadblocks on the way immortalized cell being reprogrammed into iPSC? It is known that an abnormal cell signaling, for instance, activation of MAPK (p38) [ 46 48 ], TGFβ [ 49 , 50 ], or Hippo/LATS2 [ 51 ] pathways strongly suppress the iPSC generation. From the other side, it was shown that cell immortality is a crucial and rate-limiting step towards the establishment of a pluripotent state in somatic cells.…”
Section: Resultsmentioning
confidence: 99%